2014
DOI: 10.17795/jjcdc-23368
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Management and Being Vulnerable in Older People: A Qualitative Study

Abstract: Background: With respect to high prevalence of chronic pain in the elderly, identifying factors influencing on its management process is very important. Objectives: The present study aimed to understand this management process and its setbacks in the elderly. Materials and Methods: The grounded theory approach using unstructured interviews and observation of participants were the main methods for data collection. Study participants consisted of 30 old people with chronic pain, 3 relatives, and 29 health care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Pain also influences social relationships, daily routines, and working ability resulting in financial problems (4)(5)(6). It decreases different aspects of the quality of life in both patient and family (7)(8)(9). The timely and proper pain relief leads to faster recovery, increased satisfaction and the quality of a patient's life (10).…”
Section: Cancer-related Painmentioning
confidence: 99%
“…Pain also influences social relationships, daily routines, and working ability resulting in financial problems (4)(5)(6). It decreases different aspects of the quality of life in both patient and family (7)(8)(9). The timely and proper pain relief leads to faster recovery, increased satisfaction and the quality of a patient's life (10).…”
Section: Cancer-related Painmentioning
confidence: 99%
“…Pain is a universal sensation, and at times, its intensity drives individuals to seek both the underlying cause and a suitable remedy [1,2]. The management of pain is a multifaceted process that requires collaboration and cooperation among teams and various disciplines [3,4]. Effective pain management in emergency departments and at the accident scene heavily relies on crucial cooperation between medical teams and emergency medical technicians [5].…”
Section: │ Introductionmentioning
confidence: 99%
“…These injuries often result in severe pain due to the nature of the bodily damage. Studies have indicated that the prevalence of pain among trauma victims ranges from 52% to 91% [2,4,5]. The presence of acute pain adversely impacts the care and treatment process, causing a range of adverse effects [8].…”
Section: │ Introductionmentioning
confidence: 99%
“…Pain is one of the pivotal issues in elderly as well as stroke patients (10)(11)(12). Patients with stroke experience different types of pain, including headaches, shoulder pain, and central post-stroke pins (13).…”
Section: Introductionmentioning
confidence: 99%